Comprehensive System of Personnel Development - Maryland State Dept. of Education, Baltimore. Office of Special Education; Maryland State Dept. of Education, Baltimore. Office of Special Education ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
The report describes Maryland's plan for a Comprehensive System of Personnel Development (CSPD), as mandated by P.L. 94-142, The Education for All Handicapped Children Act. Procedures are outlined by which local education agency personnel can request assistance in inservice training. A discussion of needs assessment procedures includes tables on personnel needs, projections, and current levels. Eleven training areas (including the development and implementation of individualized education programs, implications of P.L. 94-142, and assessment and services for mainstreamed handicapped students) are examined in terms of priorities, objectives, strategies, and evaluation procedures. Five categories of resources are discussed: institutions of higher education, training projects, demonstration projects, materials and equipment, and scheduled training activities. (CL)
Availability: Maryland State Department of Education, Special Education Division, Information Management Branch, P.O. Box 8717, Baltimore, Maryland 21240 ($5.25).
ERIC Note: Not available in hard copy due to marginal reproducibility of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Federal Legislation; Handicapped Children; Inservice Teacher Education; Needs Assessment; Professional Education; Program Development; State Programs; State Standards; Education for All Handicapped Children Act -- Maryland; Reports, Descriptive